(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
Our research paper will focus on the effectiveness of a requirement engineering process on organizational data warehouses used by the business analysts and managers for an effective decision making during critical situations. The global slowdown due to economic recession of 2008- 09 also affected the business climate within India and the growth rate of the Information Technology Sector. But, India being a developing economy managed to survive the economic recession to an extent. This paper focuses on the important role played by organizational data warehouse systems used for making important decisions during hard times that help in averting the impact of recession to a large extent. Recession presented businesses with a dilemma: whether to cut costs to conserve resources, or to invest in new products and processes to exploit competitor weakness. Here comes the need of correct data on which strategic decisions can be made. Thus the need of an effective requirement engineering phase is there. The policies laid down by Indian Govt. caused a total change in the way in which India does business. There are challenges facing managers together with hope for more initiative and creativity, leading to success for industry and for the whole nation. Building of efficient Data Warehouse and its maintenance is a costly and time consuming process. To overcome this problem, we should use such a technique that helps in exploring and clarifying each requirement in detail which can be considered while constructing the Data Warehouse at an early phase. The importance of an effective requirement engineering phase lies in the fact that if requirements are properly identified in the beginning, then the data warehouse would be built on an almost correct data. Correctly gathered and represented data would help the business managers to take an apt decision in the face of uncertainty to optimize the resources available at their disposal.